The Multifaceted Role of Commensal Microbiota in Homeostasis and Gastrointestinal Diseases - Marcelo José Barbosa Silva; Matheus Batista Heitor Carneiro; Brunna dos Anjos Pultz; Danielle Pereira Silva; Mateus Eustáquio de Moura Lopes; Liliane Martins dos Santos (Journal of Immunology Research)
The gastrointestinal tract houses a complex and diverse community of microbes. In recent years, an increased understanding of the importance of intestinal microbiota for human physiology has been gained. In the steady state, commensal microorganisms have a symbiotic relationship with the host and possess critical and distinct functions, including directly influencing immunity. This means that recognition of commensal antigens is necessary for the development of complete immune responses. Therefore, the immune system must face the challenge of maintaining mucosal homeostasis while dealing with undue passage of commensal or pathogenic microbes, as well as the host nutritional status or drug use. Disruption of this fine balance has been associated with the development of several intestinal inflammatory diseases. In this review, we discuss the mechanisms involved in the modulation of host-microbe interactions and how the breakdown of this homeostatic association can lead to intestinal inflammation and pathology.